Synthesis of Silver Nanoparticle Using Bio-Reductant from Wuluh Star Fruit (Averrhoa Bilimbi L.) Extract and Their Activity as Sunscreen - Muhammad Marion Akbar; Eva Marliana; Ratna Kusuma; Hindryawati, Noor (Universitas Negeri Semarang, 2025)
Synthesis of silver nanoparticles has been carried out using AgNO3 solution as precursor with wuluh star fruit extract as bioreductant and reacted under the sunlight. The synthesized silver nanoparticles were tested for its sunscreen activity. The synthesized has been done with optimation of AgNO3 precursor and bioreductant. Based on absorbances value using UV-Vis Spectrophotometer, it is shown that silver nanoparticles from 1,5 mM AgNO3 and 25% (v/v) extract are more stable than the other variation for 4 days. The characterization of silver nanoparticles using Transmission Electron Microscope (TEM) and Particle Size Analyzer (PSA) instrument result shows the morphology of rounded silver nanoparticles with diverse sizes at range 6,9 – 27,7 nm, and with average particle size of 14,8 nm. Particle Size Analyzer (PSA) instrument shows the distribution of silver nanoparticles at range under 100 nm. Sunscreen activity of silver nanoparticles shows the SPF value of 44,14 with ultra protection type and on high level. The SPF value obtained indicates that silver nanoparticles can be applied as sunscreen.